Organizing regional management mechanism sphere of physical culture and sport - Путятіна [Galina Putiatina] Галина Миколаївна; Горбачов [Vadim Gorbachev] Вадим Єгорович (Slobozhanskyi Herald of Science and Sport, 2013)
<!–[if gte mso 9]> Normal 0 false false false RU X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> Principles of the state regulation of development of the sphere of physical culture and sports are considered. Marked are the provisions of the state policy on development of the sphere of physical culture and sports. The analysis of publications on the theory and practice of state management in the sphere of physical culture and sports, which has allowed to reveal the essence of the state management mechanism is established. Problems of perfection of public-administrative relations in the sphere of physical culture and sports are indicated. The main components of the institutional mechanism for regional management are denoted. The role of regional government in the process of formation and development of sports space is stressed. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>